2002
DOI: 10.1309/t4xf-c61j-c95y-vr4q
|View full text |Cite
|
Sign up to set email alerts
|

Lobular Neoplasia in Breast Core Needle Biopsy Specimens Is Not Associated With an Increased Risk of Ductal Carcinoma In Situ or Invasive Carcinoma

Abstract: Recent reports suggest that the finding of lobular neoplasia (atypical lobular hyperplasia [ALH] or bular carcinoma in situ [LCIS]) in breast core needle biopsy specimens may be associated with an increased risk of both ductal carcinoma in situ (DCIS) or invasive carcinoma at excision. We reviewed our breast core biopsy material to see if we could confirm this finding. from 4,297 biopsies, 71 cases of lobular neoplasia lone and 35 cases of lobular neoplasia associated with typical ductal hyperplasia were ident… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
23
0
1

Year Published

2003
2003
2011
2011

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 74 publications
(24 citation statements)
references
References 6 publications
0
23
0
1
Order By: Relevance
“…Admittedly, by these criteria, a few cases of lobular carcinoma in situ involving fibroadenomas and lobular carcinoma in situ involving adenosis will be unnecessarily excised, but it is best to err on the side of caution when evaluating a mass lesion with an atypical lobular histology. Authors who have examined pure examples of lobular carcinoma in situ and atypical lobular hyperplasia and have correlated mammographic and clinical findings (4,15,17,22) have had similar findings. Again, we emphasize that cases of pleomorphic lobular carcinoma in situ and lobular carcinoma in situ with necrosis were specifically excluded from this study as we routinely recommend excision for these lobular carcinoma in situ variants.…”
Section: Discussionmentioning
confidence: 82%
“…Admittedly, by these criteria, a few cases of lobular carcinoma in situ involving fibroadenomas and lobular carcinoma in situ involving adenosis will be unnecessarily excised, but it is best to err on the side of caution when evaluating a mass lesion with an atypical lobular histology. Authors who have examined pure examples of lobular carcinoma in situ and atypical lobular hyperplasia and have correlated mammographic and clinical findings (4,15,17,22) have had similar findings. Again, we emphasize that cases of pleomorphic lobular carcinoma in situ and lobular carcinoma in situ with necrosis were specifically excluded from this study as we routinely recommend excision for these lobular carcinoma in situ variants.…”
Section: Discussionmentioning
confidence: 82%
“…There was no increased risk of IBC in the site of lesion in subsequent surgical excision of LN diagnosed in biopsy in some studies [28][29][30]. On the contrary, in other series, the rate of LN upgraded to IBC or DCIS ranged from 17% to 42% [31][32][33][34][35][36].…”
Section: Methodsmentioning
confidence: 99%
“…Some authors have previously suggested a conservative approach following a diagnosis of LN on CNB with annual examinations and mammographic surveillance [28,35,55,75,76]. Their conclusions are based on small retrospective studies.…”
Section: Conservative Approachmentioning
confidence: 99%